Predicted effects of Chinese national park policy on wildlife habitat provisioning: Experience from a plateau wetland ecosystem. (August 2020) - Peng, Wanting; Kong, Dejun; Wu, Chengzhao; Møller, Anders Pape; Longcore, Travis
Highlights: Payment for wetland ecosystems services increased habitat values for Grus nigricollis . High occurrence probability of cranes in farmland, indicating potential risk of relocation program. Roost-centered distribution pattern was detected for wintering G. nigricollis . Abstract: Understanding the ecological consequences of conservation policies on wildlife is critical for species conservation and policy implementation. China began to call for establishing a national park system in 2013 and used national parks as the predominant feature for its system of protected areas in 2019. Payment for ecosystem services (PES) and relocation constitute two important management strategies in new Chinese national parks and protected area system. To better understand the potential outcomes of such programs, we studied the winter foraging distribution of the threatened Black-necked Crane ( Grus nigricollis ), a flagship species of plateau wetlands, in Dashanbao Protected Area, SW China. Field survey data were combined with environmental variables and land use maps to model winter foraging habitat with respect to human settlements subject to PES and relocation. High suitability for foraging was mapped in the core zone around crane roosting sites, villages, and far from disturbance (e.g. main roads). Aiming at converting farmland to wetland, the payment for ecosystem services programs increased probability of occurrence of cranes by changing land cover in appropriate areas relative to crane roosts and other spatially distributed variables. Surprisingly, areas within 1 km of villages were recognized as highly suitable foraging habitats for cranes, which depend on waste grain in farmland in winter, revealing the potential risk of relocation-induced food shortage for wintering cranes. We argue that as an effective strategy in improving wildlife habitat, PES should be encouraged and relocation programs that change the existing long-term established human-wildlife interactions should be implemented only under full understanding of these relationships. As a pioneer study of the effects of conservation policy on wetland ecosystems in China, this study could shed light on conservation management for such ecosystem and species showing high dependence on a human modified environment. Future work should also focus on the social effects of these conservation strategies, especially relocation, during national park planning in China.